Leader vision and diffusion of HR policy during change. Issue 4 (13th July 2015) - Bish, Adelle; Newton, Cameron; Johnston, Kim
Abstract : Purpose: – This paper utilizes diffusion of innovation theory in order to investigate and understand the relationships between human resource (HR) policies on employee change-related outcomes. In addition, the purpose of this paper is to explore the role of leader vision at different hierarchical levels in the organization in terms of the relationship of HR policy with employee change-related outcomes. Design/methodology/approach: – This quantitative study was conducted in one large Australian government department undergoing major restructuring and cultural change. Data from 624 employees were analyzed in relation to knowledge of HR policies (awareness and clarity), leader vision (organizational and divisional), and change-related outcomes. Findings: – Policy knowledge (awareness and clarity) does not have a direct impact on employee change-related outcomes. It is the implementation of policies through the divisional leader that begins to enable favorable employee outcomes. Research limitations/implications: – Future research should employ a longitudinal design to investigate relationships over time, and also examine the importance of communication medium and individual preferences in relation to leader vision. Originality/value: – This research extends the application of diffusion of innovation theory and leader vision theory to investigate the relationship between HR policy, leader vision, and employees' change-related outcomes.